1982
DOI: 10.1288/00005537-198208000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Auditory function in acute severe head injury

Abstract: There are few clinical neuro‐otologic investigations of acute head injury. We obtained impedance and auditory brain stem response measures for 25 acute head‐injured patients, usually within 76 hours following injury. All patients were comatose at the time of assessment. Impedance abnormalities were found for over three‐fourths of the patients. Generally, they were associated with transient, reversible dysfunction, such as high negative middle ear pressure. The acoustic stapedius reflex, however, was seldom obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0

Year Published

1984
1984
2011
2011

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(31 citation statements)
references
References 25 publications
0
31
0
Order By: Relevance
“…For this reason, the Otologist should be involved in the management of the head injured as early as possible from the time of admission to the emergency unit. In severely head injured who cannot cooperate, brain stem evoked response audiometry can be helpful, 18 though this facility is not available in our center at the moment. Conductive hearing loss is much commoner because it can occur after less severe injuries and is often temporary and is related to hemotympanum or a lacerated drum.…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, the Otologist should be involved in the management of the head injured as early as possible from the time of admission to the emergency unit. In severely head injured who cannot cooperate, brain stem evoked response audiometry can be helpful, 18 though this facility is not available in our center at the moment. Conductive hearing loss is much commoner because it can occur after less severe injuries and is often temporary and is related to hemotympanum or a lacerated drum.…”
Section: Discussionmentioning
confidence: 99%
“…3 and Table 1). Hall et al (1982) reported the following relationships between ABR waveforms and functional outcome of the same patients one month later: These results indicate a correlation between ABR morphology soon after injury and neurologic functions one month later, although exceptions obviously exist for this group of 20 patients. This is one of many studies that used ABRs to assess comatose patients.…”
Section: Wavementioning
confidence: 91%
“…Auditory brainstem response (ABR) Hall et al (1982) recorded click-evoked ABRs (using a rate of 21 clicks/s) from 20 patients with severe TBI and compared their responses with ABRs from 15 control subjects. All TBI patients were comatose at the time ABRs were recorded, within 76 h post-injury.…”
Section: Aerps In Assessments Of Tbi Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…Auditory dysfunction, which may be a component of temporal bone fracture, can also occur in patients without evidence of fracture (Podoshin and Fradis, 1975). Trauma-related middle ear pathology is a common finding (Podoshin and Fradis, 1975;Hall et al, 1982). For the most part, these studies of peripheral auditory status following head injury were conducted on patients who showed good long-term neurological recovery, and could be assessed with traditional behavioral audiologic techniques.…”
mentioning
confidence: 99%